Age-related Huntington’s disease progression modeled in directly reprogrammed patient-derived striatal neurons highlights impaired autophagy - Oh, Young Mi; Lee, Seong Won; Kim, Woo Kyung; Chen, Shawei; Church, Victoria A.; Cates, Kitra; Li, Tiandao; Zhang, Bo; Dolle, Roland E.; Dahiya, Sonika; Pak, Stephen C.; Silverman, Gary A.; et al. (Nature neuroscience, 2022)
Huntington’s disease (HD) is an inherited neurodegenerative disorder with adult-onset clinical symptoms, but the mechanism by which aging drives the onset of neurodegeneration in patients with HD remains unclear. In this study we examined striatal medium spiny neurons (MSNs) directly reprogrammed from fibroblasts of patients with HD to model the age-dependent onset of pathology. We found that pronounced neuronal death occurred selectively in reprogrammed MSNs from symptomatic patients with HD (HD-MSNs) compared to MSNs derived from younger, pre-symptomatic patients (pre-HD-MSNs) and control MSNs from age-matched healthy individuals. We observed age-associated alterations in chromatin accessibility between HD-MSNs and pre-HD-MSNs and identified miR-29b-3p, whose age-associated upregulation promotes HD-MSN degeneration by impairing autophagic function through human-specific targeting of the STAT3 3′ untranslated region. Reducing miR-29b-3p or chemically promoting autophagy increased the resilience of HD-MSNs against neurodegeneration. Our results demonstrate miRNA upregulation with aging in HD as a detrimental process driving MSN degeneration and potential approaches for enhancing autophagy and resilience of HD-MSNs. Oh et al. modeled age-dependent onset of Huntington’s disease by comparing reprogrammed neurons from pre-symptomatic and symptomatic patients. They found that an age-associated miRNA led to autophagy impairment and neurodegeneration.